Association of harsh parenting and maltreatment with internet addiction, and the mediating role of bullying and social support. (March 2021) - Lo, Camilla K.M.; Ho, Frederick K.; Emery, Clifton; Chan, Ko Ling; Wong, Rosa S.; Tung, Keith T.S.; Ip, Patrick
Abstract: Growing evidence has shown that exposure to harsh parenting and child maltreatment elevate the risk of Internet addiction in adolescence. Yet, limited research has examined the mechanisms underlying this association. The present study was a cross-sectional school survey of 1204 adolescents (52.2 % male and 47.8 % female; mean age, 13.36 years) in Hong Kong. The adolescents completed a self-reported questionnaire about their exposure to bullying victimization, bullying perpetration, child maltreatment, Internet addiction, and social support. The findings showed that harsh parenting and maltreatment was significantly associated with Internet addiction. After controlling for a number of confounding factors, the results of the mediation analyses showed that family support and bullying perpetration, and family support and bullying victimization accounted for 36 % and 25 % of the effect of harsh discipline and maltreatment on Internet addiction, respectively. Effective prevention and intervention strategies for Internet addiction should target family and social vulnerabilities in adolescents.